Research paradigms in computing disciplines: a review / Nor Hafizah Abdul Razak ... [et al.] - Abdul Razak, Nor Hafizah; Abdul Talib, Noor Hasnita; Ahmad, Jasmin Ilyani (2015)
Computer science is the study of the phenomena surrounding computers. Computer science research can be one of these approaches; quantitative, qualitative and mixed method. For these approaches, researchers can apply one or more research paradigm in conducting their research work. Research paradigm is an assumption or belief system that guide the researches in completing their task. Since, there are many research paradigms underpinning of different research fields, this paper aims to provide an overview for computer science researchers in selecting an appropriate research paradigm for their study. Related papers have been examined in order to find the most commonly used research paradigms in CS/IS/IT/SE.